Attenuation mechanisms in fractured fluid-saturated porous rocks: a numerical modelling study - Caspari, Eva; Novikov, Mikhail; Lisitsa, Vadim; Barbosa, Nicolas Daniel; Quintal, Beatriz; Rubino, Jorge German; Holliger, Klaus (Wiley Blackwell Publishing, Inc, 2019)
Fil: Caspari, Eva. Universite de Lausanne; Suiza